2018
DOI: 10.24843/jei.2018.v04.i02.p03
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Istirahat Aktif Meningkatkan Kapasitas Kerja Dan Produktivitas Pekerja Bagian Pembentukan Keramik Di Btikk BPPT Bali

Abstract: Sikap kerja duduk statis dalam waktu 7 jam pada pekerja pembentukan keramik dengan mesin electric wheel di industri keramik dapat menimbulkan kelelahan dan keluhan muskuloskeletal. Tujuan penelitian ini adalah mencari solusi untuk meningkatkan kapasitas kerja dinilai dari penurunan kelelahan dan penurunan keluhan muskuloskeletal serta meningkatkan produktivitas pada pekerja bagian pembentukan keramik di BTIKK BPPT Bali. Telah dilakukan penelitian di BTIKK BPPT Bali, dengan rancangan sama subjek terhadap&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The reduction in fatigue is physiologically caused by the oxygen supply obtained after active rest and the nutritional intake obtained by the gipang workers. Regarding these findings, several researchers reported that providing adequate and appropriate active rest can reduce fatigue in workers by 17.78% (Puspadewi, et al, 2018); improving working conditions through a total ergonomic approach, namely regulating work attitudes, providing short breaks, and providing tea can reduce worker fatigue from 37.77% to 35.37% (Adiatmika, 2007); giving bananas, short breaks and stretching can reduce worker fatigue in oil palm harvesters by 23.75% (Damantalm, 2018); giving snacks in the form of sweet tea and applying short breaks to odontectomy practitioners in the Department of Dentistry can reduce fatigue 52.73% to 47.00% (Wiradharma, 2012); and the application of active rest to sculptors associated with the culture that is developing in the local community, namely at Tengai Tepet or 12.00 WITA and Sandikala or 18.30 WITA may not do work and are able to improve blood circulation so that resulting in a decrease in fatigue by 11.27% (Sutajaya & Ristiati, 2014). The results of hypothesis testing on work motivation can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…The reduction in fatigue is physiologically caused by the oxygen supply obtained after active rest and the nutritional intake obtained by the gipang workers. Regarding these findings, several researchers reported that providing adequate and appropriate active rest can reduce fatigue in workers by 17.78% (Puspadewi, et al, 2018); improving working conditions through a total ergonomic approach, namely regulating work attitudes, providing short breaks, and providing tea can reduce worker fatigue from 37.77% to 35.37% (Adiatmika, 2007); giving bananas, short breaks and stretching can reduce worker fatigue in oil palm harvesters by 23.75% (Damantalm, 2018); giving snacks in the form of sweet tea and applying short breaks to odontectomy practitioners in the Department of Dentistry can reduce fatigue 52.73% to 47.00% (Wiradharma, 2012); and the application of active rest to sculptors associated with the culture that is developing in the local community, namely at Tengai Tepet or 12.00 WITA and Sandikala or 18.30 WITA may not do work and are able to improve blood circulation so that resulting in a decrease in fatigue by 11.27% (Sutajaya & Ristiati, 2014). The results of hypothesis testing on work motivation can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Reducing CTS Complaints and the Fatigue of Rock Breaker through Ergonomics Approach by Exercising Nerve-Tendon Mobilization and Short Break 1144 (Chakrabarty et al, 2016). Short breaks can also reduce the workload, provide an opportunity for the body to recover through valodilation of blood vessels and help the heart's function to be as good as its original condition (Sutapa, Sudiarsa, & Susila, 2017), making its cells able to relax and reduce musculoskeletal disorders (Puspadewi et al, 2018), and prevent the accumulation of fatigue (Dewi et al, 2018).…”
Section: Eduvest -Journal Of Universal Studiesmentioning
confidence: 99%
“…Of the three types of fatigue associated with weakened activity, weakened motivation, physical fatigue, it was found that the intervention of nerve-tendon mobilization exercise and short break through an ergonomic approach had the most effect on the type of physical fatigue felt by workers with a decreasing effect of 11.16%. By applying the intervention of mobilization exercises to the tissues involved in the work process, it will provide opportunities for the tissues to stretch so as to reduce tissue tension, vascular reactivity, facilitate venous return, facilitate circulation of nutrients to the tissues, and result in increased blood flow to the tissues (Atya & Mansour, 2011;Coppieters & Butler, 2008;Muliarta et al, 2020;Puspadewi et al, 2018). Due to the success of this intervention in reducing musculoskeletal disorders, the workers felt less tired.…”
Section: Eduvest -Journal Of Universal Studiesmentioning
confidence: 99%
See 2 more Smart Citations